2015
DOI: 10.1016/j.celrep.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 Is Required for Inflammatory Cytokine-Driven Goblet Cell Metaplasia in the Lung

Abstract: The balance and distribution of epithelial cell types is required to maintain tissue homeostasis. A hallmark of airway diseases is epithelial remodeling, leading to increased goblet cell numbers and an overproduction of mucus. In the conducting airway, basal cells act as progenitors for both secretory and ciliated cells. To identify mechanisms regulating basal cell fate, we developed a screenable 3D culture system of airway epithelial morphogenesis. We performed a high-throughput screen using a collection of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
235
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(250 citation statements)
references
References 51 publications
(79 reference statements)
14
235
0
1
Order By: Relevance
“…[118] Both the primary tissue-derived organoids and the hPSCderived branched lung organoids contained mature cell types, but overall, these tissues lacked a proper pseudostratified epithelium. [112,[119][120][121][122][123][124] On the other hand, scaffold-transplanted lung organoids derived from hPSCs formed a tube that was organized into a pseudostratified epithelium similar to the adult airway. However, this tissue organization could not be generated in vitro.…”
Section: Airway Organoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[118] Both the primary tissue-derived organoids and the hPSCderived branched lung organoids contained mature cell types, but overall, these tissues lacked a proper pseudostratified epithelium. [112,[119][120][121][122][123][124] On the other hand, scaffold-transplanted lung organoids derived from hPSCs formed a tube that was organized into a pseudostratified epithelium similar to the adult airway. However, this tissue organization could not be generated in vitro.…”
Section: Airway Organoidsmentioning
confidence: 99%
“…Here, the basal cells form cyst structures that contain the basal cells along with other mature cell types of the airway. [112,[119][120][121][122][123][124][125] Recently, a cell surface marker specific to NKX2.1+ lung progenitors was discovered and used to sort out NKX2.1+ lung progenitors from hPSC-derived lung cultures using flow cytometry. [126,127] The single cells were placed in a Matrigel droplet overlaid with airway-specific media, which resulted in airway cysts that contain basal cells and a few other mature epithelial airway cells.…”
Section: Airway Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, recent studies have implicated Notch3 in promoting the differentiation of adult basal stem cells into parabasal progenitors and Notch1 and 2 in fate selection between secretory and ciliated linages (Rock et al, 2011b;Danahay et al, 2015;Mori et al, 2015;Pardo-Saganta et al, 2015). ChIP-Seq has shown Grhl2 occupancy of binding sites near NOT CH1, NOT CH3, JAG1, and JAG2 (Gao et al, 2013).…”
Section: Loss Of Grhl2 In Mouse Bcs Inhibits Epithelial Morphogenesismentioning
confidence: 99%
“…Recent studies have used these features to identify juxtacrine and secreted factors that direct airway epithelial cell fate in mouse tracheosphere and human bronchosphere organoids (Danahay et al, 2015;Rock et al, 2011;Tadokoro et al, 2014) expressing a Notch activity reporter, Rock and colleagues analyzed Notch activity in developing 2-to 16-cell mouse tracheospheres following initial stem cell division. They observed that single basal stem cells that express the Notch ligands Jagged and Delta divide either symmetrically to produce two basal daughter cells or asymmetrically to produce one basal daughter cell and one luminal daughter cell in which Notch signaling is active.…”
Section: Defining the Stem Cell Nichementioning
confidence: 99%